Utilize water decomposition device of optical electro -Chemistry product oxygen - CHANG CHUN; TANG KE (2017)
The utility model discloses an oxygen technical field's an utilize water decomposition device of optical electro -Chemistry product oxygen is produced to the optical electro -Chemistry, the small -sized rigid gas permeable contact lens polishing solution automatically cleaning device comprises a container, the top of container is provided with two sets of bracing pieces, the top of bracing piece is provided with the crossbeam board, the top of crossbeam board is provided with controlling means, the bottom of crossbeam board is provided with the power, the bottom of power is provided with the xenon lamp, has pegged graft hydrogen respectively and has collected cup and oxygen and collect glass in the inner chamber top left and right sides of container, the utility model discloses a power is connected with negative pole guide card and positive pole guide card, carries out the electrolysis with water, and the surface electrolysis of positive pole guide card produces oxygen, and the surface electrolysis of negativ